"Kronecker Basis" Based Average Consensus Analyses for High‐Order Linear Multi‐Agent Systems with Multiple Time Delays. Issue 4 (3rd October 2014) - Zhu, Huangyong; Cong, Yirui; Wang, Xiangke; Zhang, Daibing; Zhang, Qingjie
Abstract This paper investigates the average consensus for multi‐agent systems governed by high‐order linear dynamics with multiple time delays. Necessary and sufficient conditions for high‐order average consensus under balanced communication topology are provided by using a newly defined mathematical concept – the Kronecker basis. Furthermore, previous studies for average consensus governed by first‐order, or high‐order integrator can be regarded as special cases of our results. Simulation results are employed to demonstrate the effectiveness of our results for high‐order average consensus.